Desarrollo de biomateriales innovadores aplicables al diseño de andamios destinados a ingeniería tisular ósea - Cattalini, Juan Pablo (2016)
The aim of this thesis was to develop novel composite biomaterials made of alginate and bioactive glass nanoparticles to develop tridimensional scaffolds able to release therapeutic agents as Cu2+, Ca2+ and alendronate, to be considered for bone tissue engineering applications. Matrices in two dimensions were prepared and used in a preliminary study about the biomaterial properties, which allowed us to assay the viability of using these biomaterials in the elaboration of tridimensional and multifunctional scaffolds for bone tissue engineering. Then, it was demonstrated that the scaffolds developed had interesting properties in terms of morphology, porosity, mechanical strength, bioactivity, biodegradability and citocompatibility. In addition, it is important to note that the scaffolds showed suitable release profile of Cu2+ or Ca2+ ions, and alendronate, for promoting the proliferation of bone and endothelial cells, as well as the formation of blood vessels in an in vivo model. Furthermore, this thesis proposed the development and validation of novel and simple analytical techniques based on capillary electrophoresis to quantify the release of the therapeutic agents incorporated. These methods resulted versatile, economical and efficient for the quantification of the agents mentioned above, which were released in concentrations on the order of parts of million.